Double surface plasmon polaritons (SPPs) for sensing purposes - Lee, Kwang Hong (2011)
The thesis work describes the sensitivity enhancement of grating coupled surface plasmon resonance(GCSPR) using a novel approach - rotating the grating azimuthally to an angle where double surface plasmons polaritons (SPPs) can be excited and using an optimized polarization angle of incident light for the double SPPs excitation. This approach allows the sensitivity of GCSPR to be enhanced by fifteen times compared to non-rotated gratings and one order of magnitude higher than prism coupled surface plasmon resonance. The thesis begins with the grating fabrication technique. The gratings were fabricated by interference lithography which is used to produce highly ordered and periodic structures with in large area. Many grating replica can be fabricated by imprinting the grating master (from interference lithography) to a UV-curable polymer substrate. Subsequently, the grating was thermally evaporated with 37 nm of Ag and 7 nm of Au. This makes the grating coupler an attractive approach for fabrication of low-cost SPR sensing structures. The thesis continues with a study of surface plasmon excitation on an azimuthal rotatable grating.